Productivity, innovation and ICT in Old and New Europe - Bart van Ark; Marcin Piatkowski (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
This paper investigates the productivity performance of CEE countries vis-à-vis the EU-15 during the 1990s to detect sources of convergence between the two regions. The paper shows that changes in labour intensity have been an important source of productivity convergence during the 1990s, and are likely to remain so in the near future. It is also found that despite lower income levels, ICT capital in the CEE-10 has contributed as much to labour productivity growth as in the EU-15. Industry analysis shows that manufacturing industries that have invested heavily in ICT have been key to the restructuring process. As such ICT may therefore have been an important but probably temporary source of convergence. In the longer run the impact of ICT on growth will have to come primarily from its productive use in services. The paper therefore includes a New Economy Indicator that reflects the existence of conducive environment for continued ICT investment and diffusion. It shows that further reforms are much needed for CEE countries to enter a second convergence phase in the coming decades.
Keywords: 330; Produktivität; Innovation; Informationstechnik; EU-Mitgliedschaft; EU-Staaten